2015
DOI: 10.1016/j.nmni.2015.02.007
|View full text |Cite|
|
Sign up to set email alerts
|

The global threat of antimicrobial resistance: science for intervention

Abstract: In the last decade we have witnessed a dramatic increase in the proportion and absolute number of bacterial pathogens resistant to multiple antibacterial agents. Multidrug-resistant bacteria are currently considered as an emergent global disease and a major public health problem. The B-Debate meeting brought together renowned experts representing the main stakeholders (i.e. policy makers, public health authorities, regulatory agencies, pharmaceutical companies and the scientific community at large) to review t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
578
0
34

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 907 publications
(660 citation statements)
references
References 36 publications
(31 reference statements)
2
578
0
34
Order By: Relevance
“…84,119 Environmental contamination with antibiotics may lead emergence of antibiotic resistance and in turn creates a reservoire for antibiotic resistance genes. 120 On the other hand, it has been consistently shown that those areas where the usage is high, the resistance is widespread both in community and hospital settings.…”
Section: Acinetobacter Baumanniimentioning
confidence: 99%
See 1 more Smart Citation
“…84,119 Environmental contamination with antibiotics may lead emergence of antibiotic resistance and in turn creates a reservoire for antibiotic resistance genes. 120 On the other hand, it has been consistently shown that those areas where the usage is high, the resistance is widespread both in community and hospital settings.…”
Section: Acinetobacter Baumanniimentioning
confidence: 99%
“…7,121,122,123 Since the problem of emerging resistance is multifaceted, its prevention and control will require multiple, coordinated interventions by various parties. 119 At the hospital level; education and promotion of prudent use of antimicrobials, development and effective use of rapid and point of care diagnostic tests, devising effective surveillance systems for monitoring resistance and implementation of effective infection control programmes are essential parts of an antibiotic stewardship program. These programmes are desparetely needed and may be lacking even in hospitals in the developed part of the world.…”
Section: Acinetobacter Baumanniimentioning
confidence: 99%
“…Assim, podem contribuir para o aparecimento de infecções relacionadas à assistência à saúde (6) .As condições do paciente na admissão foram expressas pelos scores de gravidade, os quais indicam maior vulnerabilidade e deterioração dos sistemas orgânicos, culminando em maior demanda por intervenções invasivas, as quais se relacionaram ao desenvolvimento de infecções. Uma proporção crescente de infecções relacionadas à assistência à saúde está relacionada aos patógenos resistentes a antimicrobianos, como Staphylococcus aureus e bacilos Gram-negativos multirresistentes (21)(22)(23) .…”
Section: Idiscussãounclassified
“…Globally, the number of multidrug-resistant strains has increased dramatically over the past 10 years (Roca et al, 2015;Sharifi-Rad, 2016) and new more resistant strains may be expected to emerge in the coming years (McGaw et al, 2008).…”
Section: Introductionmentioning
confidence: 99%